A Dual Bi-directional Heuristic Development Framework - Murairwa, Stanley (IJRDO -JOURNAL OF MATHEMATICS, 2016)
The research designs a multi-start heuristic framework. The heuristic development approach increases the speed of convergence of heuristics to high quality optimum solutions. The multistart heuristic named the dual bi-directional (DBD) heuristic searches for the global optimum solution in four concurrent directions with a pair search starting from both the beginning and ending nodes. The search terminates when the four optimum tours connect to form an optimum round tour of all the search space nodes. Then, the DBD heuristic starts to improve the found optimum round tour in a unidirectional approach using a global search metaheuristic. The multistart heuristic framework decreases the non-convergence of the bi-directional approach by introducing the unidirectional heuristic to improve the multi-start heuristic constructed optimum round tour. The development approach will allow the convergence of the bi-directional heuristic.